(untitled) - Tan, Jackson C. (St. Louis, 1998)
This book encompasses the most concise review of all physical medicine and rehabilitation in authoritative, definitive, and up-to-date coverage. Information on pharmacology, joint and soft tissue injections, nerve blocks, and trigger point therapy are included. This approach is multidisciplinary, offering information needed for the physiatrist, physical therapist, neurologist, orthopaedist, and occupational therapist.
Keywords: Physical therapy,Vật lý trị liệu,Medical rehabilitation,Phục hồi chức năng